Educação, Cultura e Subjetividade: Deleuze e a Diferença (Education, Culture and Subjectivity: Deleuze and the Difference) - Barros, Gustavo de Almeida; Munari, Silvio Ricardo; Abramowicz, Anete (Revista Eletrônica de Educação, 2017)
This article discusses the way in which the question of Difference, in the trace of Friedrich Nietzsche's thought, becomes central to the thinking of the philosopher Gilles Deleuze whose epistemology makes for one of the axes of the Education, Culture and Subjectivity line of the Post- Graduation in Education of UFSCAR. This article discusses and analyze some concepts constructed by Deleuze that proposes a new image of thought in Philosophy, among them: difference, rhizoma, becoming and immanence, among others. Keywords: Education, Subjectivity, Difference, Deleuze. Este artigo discute a maneira pela qual a questão da Diferença, no rastro do pensamento de Friedrich Nietzsche, torna-se central no pensamento do filósofo Gilles Deleuze cuja epistemologia faz parte de um dos eixos da linha Educação, Cultura e Subjetividade do Programa de Pós-Graduação em Educação da UFSCar. Este artigo discute e tematiza alguns conceitos construídos por Deleuze que propõe uma nova imagem do pensamento na Filosofia, entre eles: diferença, rizoma, devir e imanência, entre outros. Palavras-chave: Educação, Subjetividade, Diferença, Deleuze. References ABRAMOWICZ, Anete. Arguição em defesa de tese. In: DEFESA DA TESE DE MUNARI MACHADO, Silvio R. Linhas de Errância: vidas precárias e pedagogias. 2017. 157 f. Tese (Doutorado em Educação), Universidade Federal de São Carlos, UFSCar, São Carlos, 2017. ABRAMOWICZ, Anete; LEVCOVITZ, Diana; RODRIGUES, Tatiane Cosentino. Infâncias em Educação Infantil. Pro-Posições, Campinas, v. 20, n. 3, p. 179-197, Dec. 2009. Available from <http://www.scielo.br/scielo.php?script=sci_arttext&pid=S0103-73072009000300012&lng=en&nrm=iso>. access on 19 Mar. 2017. http://dx.doi.org/10.1590/S0103-73072009000300012. AGAMBEN, Giorgio. O Que é o Contemporâneo? E Outros Ensaios. Tradução de Vinícius NicastroHonesco. Chapecó: Argo, 2009. 92 p. AGAMBEN, Giorgio. Infância e história - destruição da experiência e origem. Tradução de Henrique Burigo. Belo Horizonte: Ed. UFMG, 2005. (Coleção Humanitas). ALLIEZ, Eric. Deleuze: filosofia virtual. São Paulo: Editora 34, 1996. BRÉHIER, Émile. A Teoria dos Incorporais no Estoicismo Antigo. Tradução de Fernando Padrão de Figueiredo e José Eduardo Pimentel Filho. Transliteração e tradução do grego de Luiz Otávio de Figueiredo Montovaneli. Belo Horizonte: Autentica Editora, 2012. 111 p. DELEUZE, Gilles. Bergsonismo. Tradução de Luiz B. L. Orlandi. Rio de Janeiro: Ed. 34, 1999. 142 p. DELEUZE, Gilles. Conversações. Tradução de Peter Pál Pelbart. São Paulo: ed. 34, 1992. 232 p. DELEUZE, Gilles. Diferença e repetição. Tradução de Luiz B. L. Orlandi. Roberto Machado. 2. ed. São Paulo: Graal, 2006. 437 p. DELEUZE, Gilles. Lógica do Sentido. Tradução de Luiz Roberto Salinas. Revisão de Mary Amazonas Leite. 5. ed. São Paulo: Perspectiva, 2011. 345 p. DELEUZE, Gilles; GUATTARI, Felix. Mil Platôs. Capitalismo e esquizofrenia. Vol. 1. Tradução de Aurélio Guerra Neto e Celia Pinto Costa. São Paulo: Ed. 34, 1995. 95 p. DELEUZE, Gilles; GUATTARI, Felix. Mil Platôs. Capitalismo e esquizofrenia. Vol. 4. Tradução de Suely Rounik. São Paulo: Ed. 34, 1997. 173 p. DELEUZE, Gilles. PARNET, Claire. Diálogos. Tradução de José Gabriel Cunha. Lisboa: Relógio D’Água, 1996. 187 p. GALLO, Silvio. Deleuze e a Educação. Belo Horizonte: Autêntica Editora, 2008. 98p. HARDT, Michael. Gilles Deleuze: um aprendizado em filosofia. Trad. Sueli Cavendish. São Paulo: Editora 34, 1996. KOHAN, Walter O. Infância, estrangeiridade e ignorância: ensaios de filosofia e educação. Belo Horizonte: Autêntica, 2007. KOHAN, Walter O. Infância e Filosofia. In: Sarmento, Manuel; GOUVEIA, Maria Cristina Soares de. (Orgs), Estudos da Infância Educação e práticas sociais. Petrópolis: Vozes, 2008, p. 40-61. LAPOUJADE, David. Deleuze: os movimentos aberrantes. São Paulo: N-1 Edições, 2015. MUNARI MACHADO, Silvio R. Linhas de Errância: vidas precárias e pedagogias. 2017. 157 f. Tese (Doutorado em Educação), Universidade Federal de São Carlos, UFSCar, São Carlos-SP, 2017. PETERS. Michael. Pós-estruturalismo e filosofia da diferença: uma introdução. Trad. Tomaz Tadeu da Silva. Belo Horizonte: Autêntica, 2000. RODRIGUES, Tatiane C. Arguição em defesa de tese. In: DEFESA DA TESE DE MUNARI MACHADO, Silvio R. Linhas de Errância: vidas precárias e pedagogias. 2017. 157 f. Tese (Doutorado em Educação), Universidade Federal de São Carlos, UFSCar, São Carlos, 2017. SILVA, Tomaz. T. Tinha horror a tudo que apequenava. In: AQUINO, Júlio Groppa; REGO, Teresa Cristina (Orgs.) Deleuze pensa a educação. São Paulo: Editora Segmento, 2014. Ebook. SIMONDON, Gilbert. A gênese do indivíduo. In: PELBART, P. P.; COSTA, R. (Orgs.) Cadernos de Subjetividade: o reencantamento do concreto. Tradução de Ivana Medeiros. São Paulo: Hucitec, 2003. p. 97-117. SIMONDON, Gilbert. La Individuación. Tradução de Pablo Ires. Buenos Aires: ediciones La Cebra y Editorial Cactus, 2009. 504 p. ZOURABICHVILI, François. O Vocabulário de Gilles Deleuze. IFCH – UNICAMP (digitação e disponibilização eletrônica). Tradução de André Telles. Rio de Janeiro, 2004. 66 p. Disponível em http://claudioulpiano.org.br.s87743.gridserver.com/wp-content/uploads/2010/05/deleuze-vocabulario-francois-zourabichvili1.pdf ZOURABICHVILI, François. Deleuze: uma filosofia do acontecimento. São Paulo: Editora 34, 2016.